I Symposium on Climate Change and Biodiversity: Towards strengthening the resilience and actions required to face Climate Change in Latin America (UNED Research Journal, 2019)
Climate change is a global phenomenon with irreversible consequences if timely action is not taken. In Latin America, climate change does not receive the attention it deserves in the political, academic and citizen agenda, and information and research in Spanish is limited. The I Symposium on Climate Change and Biodiversity, which took place in August 2017 in Costa Rica, sought to generate interest and discussion on possible solutions in the face of climate change in Latin America before a multidisciplinary and inter institutional audience. The Symposium was organized into four topics: 1) Impacts on ecosystems; 2) Mitigation; 3) Adaptation; and 4) Communication and education in the face of climate change. Here, we carry out a critical synthesis of the diverse subjects presented at the symposium, some of which are developed in more detail in this special issue of UNED Research Journal. There is no question that climate change is real and that it is caused by human activities, which presents us with the opportunity to change our individual actions and policy decisions to reduce green-house gas emissions and increase their mitigation, as well as to adapt to the new reality this phenomenon brings.
Keywords: Global warming; adaptation; mitigation; governance; environment; agroecology